The Function of Hate Speech in the Context of Political Power: An Analysis of Politicians' Experiences - Tamar Doreuli; Nino Durglishvili; Nino Shoshitashvili (European Scientific Journal, ESJ, 2026)
Hate speech is a widespread phenomenon on social media and in public spaces, often contributing to violence, discrimination, and polarization in Georgia’s political discourse. In particular, Georgian politicians frequently employ hate speech. The aim of this study was to identify the circumstances and conditions that determine its use by politicians. The study is based on a qualitative research design and employs in-depth interviews. Data were collected through 20 semi-structured in-depth interviews conducted with politicians active in Georgia’s political arena, including representatives of both the governing party and the opposition. Respondents were selected using purposive sampling and included individuals of different genders, ages, and levels of political experience. The interviews focused on the reasons for, functions of, and perceptions surrounding the use of hate speech in political communication. The empirical material obtained was analyzed using thematic analysis, which enabled the identification of the main motives and social contexts underlying the use of hate speech. All interviews were conducted in accordance with ethical research principles; informed consent was obtained from all participants, and the data were processed anonymously. The analysis revealed that hate speech is often not a spontaneous emotional reaction but rather a deliberate strategy serving political competition, polarization, and the demonstration of power. Most politicians associate it with strength and influence, which explains its strategic use. This process is further facilitated by a polarized environment, a lack of effective legal regulations, and unethical media coverage. The gender analysis indicates that the intensity of hate speech directed at female politicians depends on prevailing social perceptions. Some male politicians explicitly deny using such language against women, which highlights differing interpretations of gender norms. The findings underscore the necessity of legal, educational, and cultural interventions aimed at reducing hate speech and ensuring healthy political discourse.